Hylocereus polyrhizus effect on catalase and malondialdehyde in rats with oxidative stress - SRI WAHDANINGSIH; EKA KARTIKA UNTARI (Jurnal Natural, 2021)
The excessive production of free radicals causes oxidative damage and degenerative diseases. Whereas, catalase is a macromolecule with a specific activity, but Malondialdehyde (MDA) is a small molecule with no activity. The peels of red dragon fruit (H. polyrhizus) are potential to be natural exogenous antioxidants. This research aimed to determine the effects of methanol fraction from H. polyrhizus peels on catalase activity and MDA level. The peel was macerated using chloroform and fractionated using methanol. The stress condition was done through five-day fasting and ten-minute swimming per day. The activity of catalase and MDA was measured using UV-Vis spectrophotometer. Thirty five rats were divided into 7 groups: normal, negative, dose I (5 mg/200gBW), dose II (10 mg/200gBW), dose III (20 mg/200gBW), positive control (quercetin) (4 mg/200gBW) and vitamin E (17.64 mg/kg). The activity of catalase in the normal, negative, vitamin E, and quercetin, dose I, II, and II respectively were: 28.37; 7.8; 24.85; 34.33; 59.92; 28.18; and 70.85 Unit/mL. The average MDA level in the groups respectively were: 0.042; 0.051; 0.034; 0.042; 0.037; 0.033; 0.030 μg/mL. The result of One Way ANOVA test showed that the catalase activity in dose III was significantly different than normal group; the MDA levels in all groups were significantly different than normal group. This research revealed that methanol fraction from H. polyrhizus peels is a potent antioxidant for its capacity to increase the activity of catalase and reduce the MDA level in rats with oxidative stress.